Biosorption Study of Potential Fungi for Copper Remediation from Peninsular Malaysia - Ong, Ghim Hock*; Ho, Xin Han*; Shamkeeva, Saikal*; Savithri Fernando, Ambagahage Shimen Manasha*; Wong, Ling Shing* (Wiley Online Library, 2017)
The ability to grow in heavy metal contaminated areas and absorb heavy metals from the environment make fungi a potentially viable biological-based technology for remediating hazardous heavy metals in soil. In this study, 10 fungi from a copper (Cu)-polluted area in Malaysia were isolated, with the four highest growth fungi identified as Simplicillium subtropicum, Fusarium solani, Aspergillus tamari, and Aspergillus niger. Results from toxicity and biosorption testing showed that A. niger and F. solani grew the fastest in the presence of Cu, but exhibited lower Cu uptake per unit of biomoass. In contrast, A. tamarii and S. subtropicum had lower growth rates, but showed better uptake of Cu per unit of biomass. S. subtropicum was identified as the best species for bioremediation because it had the highest Cu uptake and positive growth measured in the presence of Cu at concentrations below 100 mg/L. A niger proved to be most suitable for bioremediation if the concentration of Cu exceeds 100 mg/L.